The Sound of Grasp Affordances: Influence of Grasp‐Related Size of Categorized Objects on Vocalization. Issue 10 (28th September 2019) - Vainio, Lari; Vainio, Martti; Lipsanen, Jari; Ellis, Rob
Abstract: Previous research shows that simultaneously executed grasp and vocalization responses are faster when the precision grip is performed with the vowel [i] and the power grip is performed with the vowel [ɑ]. Research also shows that observing an object that is graspable with a precision or power grip can activate the grip congruent with the object. Given the connection between vowel articulation and grasping, this study explores whether grasp‐related size of observed objects can influence not only grasp responses but also vowel pronunciation. The participants had to categorize small and large objects into natural and manufactured categories by pronouncing the vowel [i] or [ɑ]. As predicted, [i] was produced faster when the object's grasp‐related size was congruent with the precision grip while [ɑ] was produced faster when the size was congruent with the power grip (Experiment 1). The effect was not, however, observed when the participants were presented with large objects that are not typically grasped by the power grip (Experiment 2). This study demonstrates that vowel production is systematically influenced by grasp‐related size of a viewed object, supporting the account that sensory‐motor processes related to grasp planning and representing grasp‐related properties of viewed objects interact with articulation processes. The paper discusses these findings in the context of size–sound symbolism, suggesting that mechanisms that transform size‐grasp affordances into corresponding grasp‐ and articulation‐related motor programs might provide a neural basis for size‐sound phenomena that links small objects with closed‐front vowels and large objects with open‐back vowels.